2011
DOI: 10.1007/s10236-011-0404-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of meteorological variation on the upwelling system off eastern Hainan during summer 2007–2008

Abstract: The influence of meteorological variation, i.e., typhoon and precipitation events, on the coastal upwelling off the eastern Hainan Island was studied based on observations taken during two upwelling seasons. The observations were made in August 2007 and July 2008, respectively. We found that, in principle, similar structure of sea surface temperature and bottom temperature prevailed in both observational periods, providing evidence that upwelling events occur frequently during the summer monsoon along the east… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The sampling period is in summer and therefore, this study does not consider the mixing process induced by alongshore currents. This assumption is reasonable because previous studies have shown that currents perpendicular to the coastline other than alongshore current is dominant in HEU during the summertime (Hu & Wang, ; Jing et al, ; Lin et al, ; J. Su et al, ). Based on oceanographic settings and dominant radium sources, two scenarios are considered when deriving water residence time of upper layer of HEU with radium isotopes: with and without influences of coastal upwelling.…”
Section: Methodsmentioning
confidence: 81%
See 4 more Smart Citations
“…The sampling period is in summer and therefore, this study does not consider the mixing process induced by alongshore currents. This assumption is reasonable because previous studies have shown that currents perpendicular to the coastline other than alongshore current is dominant in HEU during the summertime (Hu & Wang, ; Jing et al, ; Lin et al, ; J. Su et al, ). Based on oceanographic settings and dominant radium sources, two scenarios are considered when deriving water residence time of upper layer of HEU with radium isotopes: with and without influences of coastal upwelling.…”
Section: Methodsmentioning
confidence: 81%
“…The low temperature zone expands at 25 m and reaches the maximum at the depth of 50 m. At the layers of 75 and 100 m, the lower temperature zones are reduced to the northeastern zone. The lower temperature zones at the nearshore coastal areas are mainly caused by the Ekman transport driven by alongshore wind during the summer seasons, and the lower temperature core at the northeastern coastal was speculated to be resulted from Ekman pump driven by the cyclonic wind stress curl (Jing et al, ; Lin et al, ; J. Su et al, ). Salinity and density anomaly gradually decline with depths in each layer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations